The rules of wealth a personal code for prosperity and plenty - Templar, Richard 1950-2006 (Pearson Education Limited, 2015)
A personal code for prosperity and plenty. Some people seem to find money so easy. Easy to make, easy to hold on to, and easy to grow. The rest of us just find it easy to spend. Is it all luck, or is there something rich people know or do that we don't? Is it something we could all learn? The answer is a resounding yes. They know the Rules of wealth. The Rules of wealth are the guiding principles that will help you generate more money, handle it more wisely, grow it more effectively, and use it to live a happier, more fulfilling and comfortable life. In this new edition of the worldwide bestseller, Richard Templar has added 10 brand new Rules to make your life even more rewarding. If you dream of having enough money never to worry about it ever again, you need The Rules of Wealth.